HUBUNGAN ANTARA SELF-EFFICACY DENGAN BURNOUT PADA PENGAJAR TAMAN KANAK-KANAK SEKOLAH â€œXâ€ DI JAKARTA - Hartawati, Dewi; Mariyanti, Sulis (Jurnal Psikologi, 2014)
AbstractTeacher needs to have a self-efficacy as the main factor which can help them to perform well when they have to face the demand as a teacher. Teachers who have lack of Self-efficacy in doing their job as a teacher tend to have stress and get burnout. Therefore, there is a correlation between Self-efficacy and Burnout. This research is a quantitative, with statistical techniques correlations. The sample in this study involved 40 of The â€œXâ€ Preschool Teacher in Jakarta. Sample was taken by census method. The instrument used are self-efficacy and burnout scale with reliability coefficient (Î±) 0,965 for Burnout variable with 45 valid items and (Î±) 0,978 for Self-efficacy variable with 58 valid items.The results showed the strong correlation coefficient of -0,691 with sig. 0,000 (p < 0.01), which means that there is a negative strong significant correlation between Self-efficacy with Burnout on The â€œXâ€ Preschool teacher, belonging to the categorisation is moderately, where Self-efficacy is high and the level of Burnout on the â€œXâ€ Preschool teacher belonging to the categorisation is moderately, where Burnout is low. Burnout analysis with age, marital status, education and job using cross-tabulation (p>0,005) showed there is no correlation between age, marital satus, education and job with Burnout.Keywords: teacher, self-efficacy, burnoutÂ AbstrakFaktor yang perlu dimiliki oleh seorang pengajar diantaranya adalah Self-efficacy yang dapat membantu pengajar menghadapi kendala dalam menjalani tuntutan tugasnya. Ketidakyakinan pengajar akan kemampuan dirinya dalam menghadapi tuntutan tugasnya dapat menimbulkan stres dan menyebabkan Burnout. Penelitian ini bersifat kuantitatif korelasioal non-eksperimental. Sampel penelitian berjumlah 40 pengajar TK sekolah â€œXâ€ di Jakarta.Â  Teknik sampling yang digunakan ada-lah sampel jenuh. Instrumen penelitian yang digunakan adalah kuesioner Burnout dan kuesioner Self-efficacy. Masing-masing kuesioner memiliki tingkat reliabilitas (Î±) 0,965 untuk variabel Burnout dengan 45 item valid dan (Î±) 0,978 untuk variabel Self-efficacy dengan 58 item valid. Hasil penelitian menunjukkan koefisien korelasi kuat sebesar -0,691 dengan sig. 0,000 (p < 0,01), artinya ada hubungan negatif kuat signifikan antara Self-efficacy dengan Burnout pada pengajar TK sekolah â€œXâ€. Pengajar TK sekolah â€œXâ€ memiliki Self-efficacy tinggi lebih banyak dibandingkan yang memiliki Self-efficacy rendah. Burnout pada pengajar TK sekolah â€œXâ€ lebih banyak memiliki Burnout rendah dibandingkan Burnout tinggi. Berdasarkan analisis hubungan Burnout dengan data penunjang yang menggunakan tabulasi silang (p > 0,005) menunjukkan tidak terdapat hubungan antara Burnout dengan usia, status, pendidikan dan jabatan pada pengajar TK sekolah â€œXâ€ di Jakarta.Kata kunci: pengajar, self-efficacy, burnout